Quasi-Feminism and Identity Exploration in the film Laapata Ladies - Dhiman, Bharat (The journal of religion and film, 2025)
The film Laapata Ladies (2024), directed by Kiran Rao, is a social commentary revolving around misogyny and the socio-cultural barriers faced by women in rural India, serving as a brilliant ode to womanhood and conveying its message effectively without any melodrama, thereby reflecting social realities at a ground level. The film explores the protagonists' inner dilemmas, constraints, struggles, and hardships, advocating the cause for inclusivity from a quasi-feminist perspective, poignantly urging us to re-examine our perspectives and stirring conversations around the need for women to establish their own identities, away from the standard kaleidoscope of the male gaze.